2023
DOI: 10.1002/ajh.26984
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes: 2023 update on diagnosis, risk‐stratification, and management

Guillermo Garcia‐Manero

Abstract: Disease overview: The myelodysplastic syndromes (MDS) are a very heterogeneous group of myeloid disorders characterized by peripheral blood cytopenias and increased risk of transformation to acute myelogenous leukemia (AML). MDS occurs more frequently in older males and in individuals with prior exposure to cytotoxic therapy. Diagnosis: Diagnosis of MDS is based on morphological evidence of dysplasia upon visual examination of a bone marrow aspirate and biopsy. Information obtained from additional studies such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 181 publications
0
28
1
Order By: Relevance
“…Leitch et al. reported that patients with transfusion-dependent LR-MDS had significantly longer median overall survival time after receiving ICT from the onset of transfusion dependence compared with those who did not [ 198 ], and the survival advantage persisted even after conducting a matched pair analysis that accounted for age, frailty, comorbidities, and R-IPSS [ 199 ]. Recent studies of 2200 patients with MDS, of whom 224 received ICT, also confirmed that ICT can ameliorate the overall survival and hematopoiesis of transfused patients with LR-MDS.…”
Section: Pathophysiology Of Mdsmentioning
confidence: 99%
“…Leitch et al. reported that patients with transfusion-dependent LR-MDS had significantly longer median overall survival time after receiving ICT from the onset of transfusion dependence compared with those who did not [ 198 ], and the survival advantage persisted even after conducting a matched pair analysis that accounted for age, frailty, comorbidities, and R-IPSS [ 199 ]. Recent studies of 2200 patients with MDS, of whom 224 received ICT, also confirmed that ICT can ameliorate the overall survival and hematopoiesis of transfused patients with LR-MDS.…”
Section: Pathophysiology Of Mdsmentioning
confidence: 99%
“…Validation specificity ranged between 92% and 100% and sensitivity between 75 and 100% [ 78 ]. Serum-based Raman spectral analysis could be a rapid label-free identification tool that would improve the diagnostic efficiency of MDS and AML as MDS can develop into secondary AML and its diagnostics is mostly exclusive [ 79 ].…”
Section: Applications Of Raman Spectroscopy In Medical Research and C...mentioning
confidence: 99%
“…The etiology of this disease is unknown and may be related to genetic, infectious or immune factors ( 2 ). In individuals aged ≥60 years, the prevalence was 7–35 cases per 100,000 individuals over the last two decades ( 3 ). MDS can be categorized into subtypes that are associated with lower or higher risk for acute myeloid leukemia transformation, which assists with therapy selection.…”
Section: Introductionmentioning
confidence: 99%
“…For those with higher-risk MDS, hypomethylating agents such as azacitidine, or decitabine, are first-line therapy. Hematopoietic cell transplantation is considered for higher-risk patients and represents the only potential cure ( 3 ). IgG4-related disease (IgG4-RD) is an immune-mediated progressive inflammatory disease associated with fibrosis ( 4 ), a specific organ predisposition involving the submandibular glands, parotid glands, lymph nodes, liver, and biliary tract ( 5 ).…”
Section: Introductionmentioning
confidence: 99%